2013
DOI: 10.1016/j.neuroscience.2013.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate improves locomotor impairment and early mortality in a rotenone-induced Drosophila model of Parkinson’s disease

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder primarily affecting the dopaminergic neurons in the nigrastriatal pathway resulting in debilitating motor impairment in both familial and sporadic cases. Histone deacetylase (HDAC) inhibitors have been recently implicated as a therapeutic candidate because of their ability to correct the disrupted HDAC activity in PD and other neurodegenerative diseases. Sodium butyrate (SB), an HDAC inhibitor, reduces degeneration of dopaminergic neurons in a mutant alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(107 citation statements)
references
References 39 publications
2
104
1
Order By: Relevance
“…cells and other cellular models of midbrain DA neurons in vitro (Chen et al 2006;Chen et al 2007;Collins et al 2015;Gardian et al 2004;Kidd and Schneider 2010;Kidd and Schneider 2011;Kontopoulos et al 2006;Outeiro et al 2007;St Laurent et al 2013;Wu et al 2008;Zhu et al 2014). However, to our knowledge, the present study is the first to show that a selective HAT activator can induce similar neurotrophic effects in the SH-SY5Y neuronal cell line.…”
Section: A Number Of Reports Have Documented Neurotrophic Effects Of mentioning
confidence: 54%
See 1 more Smart Citation
“…cells and other cellular models of midbrain DA neurons in vitro (Chen et al 2006;Chen et al 2007;Collins et al 2015;Gardian et al 2004;Kidd and Schneider 2010;Kidd and Schneider 2011;Kontopoulos et al 2006;Outeiro et al 2007;St Laurent et al 2013;Wu et al 2008;Zhu et al 2014). However, to our knowledge, the present study is the first to show that a selective HAT activator can induce similar neurotrophic effects in the SH-SY5Y neuronal cell line.…”
Section: A Number Of Reports Have Documented Neurotrophic Effects Of mentioning
confidence: 54%
“…We and others have shown that pan-and class-specific HDAC inhibitors can protect DA neurons (Chen et al 2006;Chen et al 2007;Collins et al 2015;Gardian et al 2004;Kidd and Schneider 2010;Kidd and Schneider 2011;Kontopoulos et al 2006;Outeiro et al 2007;St Laurent et al 2013;Wu et al 2008;Zhu et al 2014) and sympathetic neurons (Collins et al 2015) in experimental models of PD. The potential of this approach for clinical translation is highlighted by an ongoing Phase I clinical trial of the FDA-approved drug Glycerol Phenylbutyrate (a HDAC inhibitor) which is exploring the potential of this drug to increase the removal of α-synuclein from the brain (NCT02046434) (for recent reviews see Harrison and Dexter 2013;Schneider et al 2013;Valor et al 2013).…”
Section: Introductionmentioning
confidence: 95%
“…In recent times, Drosophila system is extensively employed not only to obtain basic mechanistic data on the pathophysiology of several neurodegenerative diseases, but also as a primary platform to screen various putative phytochemicals for their neuromodulatory potency against experimentallyinduced neurodegeneration (Laurent et al 2013;Sudati et al 2013). Rotenone (ROT), a well-established mitochondrial toxin is often used as a model chemical, since it reproduces some important aspects of PD pathology both in Drosophila and rodent models (Coulom and Birman, 2004;Canon and Greenamyere 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, the targeted downregulation of SIRT2 has been shown to rescue α-synuclein toxicity and dopaminergic cell loss in flies and in primary mesencephalic culture [31]. Moreover, toxicity associated with nuclear-targeted α-synuclein in both flies and SH-SY5Y cells can be rescued by employing HDAC inhibitors (HDACIs) [22,31,32]. In addition, oxidative stress is known to cause nuclear translocation of α-synuclein, which then binds to the promoter element (peroxisome proliferatorreceptor gamma coactivator-1) PGC1-αto to cause histone deacetylation and lowered PGC1-α levels [33].…”
Section: Epigenetic Modulation In Familial Parkinson's Diseasementioning
confidence: 66%